Phenotypic plasticity underlies local invasion and distant metastasis in colon cancer - Sacchetti, Andrea; Teeuwssen, Miriam; Verhagen, Mathijs; Joosten, Rosalie; Xu, Tong; Stabile, Roberto; van der Steen, Berdine; Watson, Martin M.; Gusinac, Alem; Kim, Won Kyu; Ubink, Inge; Van de Werken, Harmen Jg; et al. (ELIFE SCIENCES PUBLICATIONS LTD, 2021)
Phenotypic plasticity represents the most relevant hallmark of the carcinoma cell as it bestows it with the capacity of transiently altering its morphological and functional features while en route to the metastatic site. However, the study of phenotypic plasticity is hindered by the rarity of these events within primary lesions and by the lack of experimental models. Here, we identified a subpopulation of phenotypic plastic colon cancer cells: EpCAM(lo) cells are motile, invasive, chemo-resistant, and highly metastatic. EpCAM(lo) bulk and single-cell RNAseq analysis indicated (1) enhanced Wnt/beta-catenin signaling, (2) a broad spectrum of degrees of epithelial to mesenchymal transition (EMT) activation including hybrid E/M states (partial EMT) with highly plastic features, and (3) high correlation with the CMS4 subtype, accounting for colon cancer cases with poor prognosis and a pronounced stromal component. Of note, a signature of genes specifically expressed in EpCAM(lo) cancer cells is highly predictive of overall survival in tumors other than CMS4, thus highlighting the relevance of quasi-mesenchymal tumor cells across the spectrum of colon cancers. Enhanced Wnt and the downstream EMT activation represent key events in eliciting phenotypic plasticity along the invasive front of primary colon carcinomas. Distinct sets of epithelial and mesenchymal genes define transcriptional trajectories through which state transitions arise. pEMT cells, often earmarked by the extracellular matrix glycoprotein SPARC together with nuclear ZEB1 and beta -catenin along the invasive front of primary colon carcinomas, are predicted to represent the origin of these (de)differentiation routes through biologically distinct cellular states and to underlie the phenotypic plasticity of colon cancer cells.
Keywords: TO-MESENCHYMAL TRANSITION; COLORECTAL-CANCER; STEM-CELLS; GENE-EXPRESSION; TUMOR; TRANSPLANTATION; PROGRESSION; MUTATIONS; HALLMARKS; SEQUENCE